Medication Discrepancies and Regimen Complexity in Decompensated Cirrhosis: Implications for Medication Safety - Kelly L. Hayward; Patricia C. Valery; Preya J. Patel; Catherine Li; Leigh U. Horsfall; Penny L. Wright; Caroline J. Tallis; Katherine A. Stuart; Michael David; Katharine M. Irvine; Neil Cottrell; Jennifer H. Martin; et al. (MDPI AG, 2021)
Discrepancies between the medicines consumed by patients and those documented in the medical record can affect medication safety. We aimed to characterize medication discrepancies and medication regimen complexity over time in a cohort of outpatients with decompensated cirrhosis, and evaluate the impact of pharmacist-led intervention on discrepancies and patient outcomes. In a randomized-controlled trial (n = 57 intervention and n = 57 usual care participants), medication reconciliation and patient-oriented education delivered over a six-month period was associated with a 45% reduction in the incidence rate of 'high' risk discrepancies (IRR = 0.55, 95%CI = 0.31-0.96) compared to usual care. For each additional 'high' risk discrepancy at baseline, the odds of having ≥ 1 unplanned medication-related admission during a 12-month follow-up period increased by 25% (adj-OR = 1.25, 95%CI = 0.97-1.63) independently of the Child-Pugh score and a history of variceal bleeding. Among participants with complete follow-up, intervention patients were 3-fold less likely to have an unplanned medication-related admission (adj-OR = 0.27, 95%CI = 0.07-0.97) compared to usual care. There was no association between medication discrepancies and mortality. Medication regimen complexity, frequent changes to the regimen and hepatic encephalopathy were associated with discrepancies. Medication reconciliation may improve medication safety by facilitating communication between patients and clinicians about 'current' therapies and identifying potentially inappropriate medicines that may lead to harm.